十二指腸への遠隔転移を認めた上顎歯肉血管肉腫の1例 - 小牧, 完二; 長谷川, 正午; 山本, 知由; 奥村, 嘉英; 町田, 純一郎; 木村, 将士 (日本口腔外科学会雑誌, 2014)
Angiosarcoma is a rare malignant tumor of endothelial cell origin that accounts for less than 0.1％ of all head and neck malignancies. Although angiosarcoma can occur in the head and neck region, the most common sites are the skin of the scalp and face. The occurrence of a primary angiosarcoma in the oral cavity is extremely rare. This report describes a case of angiosarcoma of the maxillary gingiva that metastasized to the duodenum. A 64-year-old Japanese man consulted our hospital because of a maxillary gingival mass. The lesion was a protruded multinodular mass with a maximum diameter of 1.5 cm and was localized to the gingival mucosa of the left side of the maxilla. On the basis of histological examination, the lesion was diagnosed as angiosarcoma, and the patient received partial maxillectomy under general anesthesia, including a 2.0-cm margin of normal tissue. Immunohistochemical examination revealed that the tumor cells were positive for CD31, CD34, and vimentin, and the Ki-67 index was up to 40％． Although local recurrence was not detected after the initial operation, distant metastasis to the duodenum appeared after 1 year 7 months. The patient and his family refused further treatment, and we therefore provided best supportive care. The patient died 2 years 1 month after the initial operation.